(untitled) (Journal of Science and Technology, 2016)
Across-sectional, descriptive study to determine diarrhoeal incidence and oral rehydration practices by 160 mothers sampled from mothers who attended ante-natal and post-natal clinics in the Obuasi district is presented. The purpose of the study was to determine diarrhoeal morbidity and mortality patterns, and ascertain the use of Oral Rehydration Therapy and other diarrhoeal management practices to provide the basis for a more effective diarrhoeal control programme. Interviews through questionnaire revealed that diarrhoeal morbidity in the area is quite high (37.1%). Though mothers are aware of the use of Oral Rehydration Salts (ORS), only 16.4% use them. Instead, enema and the use of a combination of herbs and other ’medicines.’ is the common practice. A programme to educate the mothers on the importance of preventing excessive dehydration so as to reduce mortality from diarrhoeal is recommended.